2017
DOI: 10.4209/aaqr.2017.07.0233
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Organic Pollutant Reductions from a Diesel Engine Generator Fueled with Waste Cooking Oil-based Biodiesel Blended with Butanol and Acetone

Abstract: This investigation focuses on the effects on emissions of persistent organic pollutants (POPs) (polychlorinated dibenzop-dioxins and dibenzofurans (PCDD/Fs), polychlorinated biphenyls (PCBs), polybrominated dibenzo-p-dioxins and dibenzofurans (PBDD/Fs) and polybrominated diphenyl ethers (PBDEs)) from a diesel engine fuelled by 20 vol% waste cooking oil-based biodiesel (W20) blended with various fractions of dehydrate/hydrous butanol (B/B′) and acetone (A/A′). The emission concentrations of the POPs were in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…ACE has been used in mixtures with biodiesel to reduce pollutant emission and to enhance its flow properties at low temperatures [ 28 , 29 , 30 ]. Moreover, ternary blends, such as acetone/bioethanol/diesel, have been investigated in diesel engines [ 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…ACE has been used in mixtures with biodiesel to reduce pollutant emission and to enhance its flow properties at low temperatures [ 28 , 29 , 30 ]. Moreover, ternary blends, such as acetone/bioethanol/diesel, have been investigated in diesel engines [ 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…The PM 2.5 levels in exhaust gas from D100, W20 and W40 were 16.3 ± 2.04, 13.8 ± 1.71, and 14.1 ± 2.14 mg Nm -3 , respectively, at 1.5 kW load, and 30.2 ± 6.43, 23.2 ± 3.55, and 24.0 ± 3.40 mg Nm -3 , respectively, at 3.0 kW load (as shown in Table 2). Obviously, the PM 2.5 concentrations were higher at 3.0 kW than at 1.5 kW when using D100, W20 or W40, because more fuel was consumed (higher fuel consumption) at 3.0 kW, causing more PM 2.5 mass emissions at the higher engine load (Tsai et al, 2017). Reductions in PM 2.5 emissions by using W20 and W40 in comparison to D100 were 14.4% and 14.0%, respectively, at 1.5 kW load, and 22.1% and 20.3%, respectively, at 3.0 kW load.…”
Section: Effect Of Biodiesel On Pm 25 Emission and Engine Performancementioning
confidence: 99%
“…A similar study by Zhou et al (2019) also indicated that OCPs such as p,p'-DDT and p,p'-DDE are predominant in Taiwan. PBDEs coming from diesel vehicles, which is the largest source of PM 2.5 in Tainan City (Lu et al, 2019), has the highest emission concentration among other pollutants like PCDD/Fs, polychlorinated biphenyls (PCBs), polybrominated dibenzo-p-dioxins and dibenzofurans (PBDD/Fs) (Tsai et al, 2017). Therefore, these dangerous POPs can be found in vicinities with PM 2.5 and can possibly risk human health living near the areas.…”
Section: Introductionmentioning
confidence: 99%